Physiological stress response associated with elevated CO2 and dissolved iron in a phytoplankton community dominated by the coccolithophore Emiliania huxleyi. - Segovia-Azcorra, María; Lorenzo, M. Rosario; Íñiguez Moreno, Concepción; García-Gómez, Candela (Inter-Research Science Publisher, 2018)
We exposed a natural phytoplankton community to combined present (390 µatm, low carbon [LC]) and future CO2 levels predicted for the year 2100 (900 µatm, high carbon [HC]), and ambient (4.5 nM, -DFB [desferoxamine B]) and high (12 nM, +DFB) dissolved iron (dFe) levels, for 25 d in mesocosms. We report on the physiological response of the community dominated by the coccolithophore Emiliania huxleyi. The community structure shifted on Day 10, leading to 2 different phases (1 and 2), i.e. before and after Day 10, respectively. We focussed on the massive bloom of E. huxleyi that developed in Phase 2, in the LC+DFB treatment. In high dFe conditions, pigments and photosynthetic parameters increased compared to the control (LC-DFB). Cell death was only detected during the community shift (Days 10-12) and mostly increased in the presence of high CO2. The accumulation of reactive oxygen species (ROS) decreased under high dFe, pointing to an efficient, rather than a stressed, metabolism. DNA lesions, caused by excess irradiance, were minimised under high Fe. E. huxleyi is known for its low Fe requirements for growth. However, we demonstrate that Fe is essential to E. huxleyi for DNA repair and ROS management, and to maintain optimal functioning of the photosynthetic machinery, with implications for carbon cycling and future ecosystem functioning.
https://openpolicyfinder.jisc.ac.uk/id/publication/13299
Keywords: Oceanografía; Mesocosms; Photosynthesis; Electron Transport Chain; Pigments; Cell Death; Oxidative Stress; DNA damage; Emiliana huxleyi